Evaluasi Keselamatan Kerja Listrik Laboratorium Permesinan Kapal Universitas Maritim AMNI Semarang Dengan Metode Analitycal Network Process (ANP) - Sunu Arsy; Bayu Murti (Dinamika Bahari, 2021)
In the operation of electrical components in the ship engineering laboratory of the Maritime University of AMNI Semarang, various kinds of protection are needed. Errors in installing and operating electrical equipment can reduce protection. This protection aims to improve the safety of electrical work in ship engineering laboratories. And in the application of electrical work safety, it is necessary to evaluate based on the 2000 Electrical Installation General Requirements standard (PUILL 2000). The purpose of this study was to evaluate the use of the laboratory of the Maritime University of AMNI Semarang in the aspect of work safety. Based on the results of the evaluation, the criteria for electrical work safety are determined, namely: protection for safety, protection from overvoltages and currents, protection from thermal effects, and protection from fault currents. After the evaluation was carried out, alternatives were found to improve electrical safety: standard operating procedure (SOP), an inspection of cable installations, checking MCB panels and switches. The criteria and alternatives obtained then processed using the software super decision ver.2.10.0 with the Analytical Network Process (ANP) method so that the priority results of electrical safety improvements in the ship engineering laboratory of AMNI Maritime University Semarang are: repair of SOP 63.7%, cable installation 25.8%, MCB panel, and 10.5% switch.